Characterization of a new cytotoxin that contributes to Staphylococcus aureus pathogenesis - DuMont, Ashley L. (2010)
Staphylococcus aureus is an important pathogen that continues to be a significant global health threat due to the prevalence of methicillin resistant S. aureus strains (MRSA). The pathogenesis of this organism is partly attributed to the production of a large repertoire of cytotoxins that target and kill innate immune cells, which provide the first line of defense against S. aureus infection. Here we demonstrate that leukocidin A/B (LukAB) is required and sufficient for the ability of S. aureus, including MRSA, to kill human neutrophils, macrophages and dendritic cells. LukAB targets the plasma membrane of host cells resulting in cellular swelling and subsequent cell death. We found that S. aureus lacking lukAB are severely impaired in their ability to kill phagocytes during bacteria-phagocyte interaction, which in turn renders the lukAB-negative staphylococci more susceptible to killing by neutrophils. Notably, we show that lukAB is expressed in vivo within abscesses in a murine infection model and that it contributes significantly to pathogenesis of MRSA in an animal hosts. Collectively, these results extend our understanding of how S. aureus avoids phagocyte-mediated clearance, and underscore LukAB as an important factor that contributes to staphylococcal pathogenesis.